2004
DOI: 10.1111/j.1365-2982.2004.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the utility of colorectal function tests and Rome II criteria in dyssynergic defecation (Anismus)

Abstract: Although 30-50% of constipated patients exhibit dyssynergia, an optimal method of diagnosis is unclear. Recently, consensus criteria have been proposed but their utility is unknown. To examine the diagnostic yield of colorectal tests, reproducibility of manometry and utility of Rome II criteria. A total of 100 patients with difficult defecation were prospectively evaluated with anorectal manometry, balloon expulsion, colonic transit and defecography. Fifty-three patients had repeat manometry. During attempted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
246
2
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(273 citation statements)
references
References 27 publications
11
246
2
14
Order By: Relevance
“…Moreover, whether patterns recorded using SARM and HRM are entirely comparable remains unknown. Currently, dyssynergic defecation classification using SARM relies on an expert-based pattern-recognition process proposed by Rao et al [2] . Recently, Ratuapli et al set out to determine whether HRM could identify DD phenotypes using principal components logistical modeling (PC) in patients with chronic constipation [12] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, whether patterns recorded using SARM and HRM are entirely comparable remains unknown. Currently, dyssynergic defecation classification using SARM relies on an expert-based pattern-recognition process proposed by Rao et al [2] . Recently, Ratuapli et al set out to determine whether HRM could identify DD phenotypes using principal components logistical modeling (PC) in patients with chronic constipation [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Type I is characterized by a paradoxical increase in the residual anal pressure in the presence of adequate propulsive pressure, that is, increase in intrarectal pressure (45 mm Hg) type II is characterized by an inability to generate adequate expulsive forces, ie, no increase in intrarectal pressure, together with a paradoxical increase in residual intraanal pressure. Type III is characterized by generation of adequate expulsive forces, but absent or incomplete (<20%) reduction in intraanal pressure and type IV is characterized by an inability to generate adequate expulsive forces, that is, no increase in intrarectal pressue and absence of incomplete reduction in residual intraanal pressure [2] . The University of Iowa Institutional Review Board approved the study protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 It was concluded that a negative test was useful for identifying patients who do not have dyssynergia. However, Rao et al 39,51 found that many patients with dyssynergia could expel the balloon, and they expressed the view that a normal test could not exclude the possibility of a defecatory disorder. BET can be helpful in predicting defecatory disorders, but other rectoanal function tests should be performed to confirm a diagnosis.…”
Section: Statement: Anorectal Manometry Is Useful For Diagnosing Defementioning
confidence: 99%
“…1 One study reported a sensitivity of 88%, a specificity of 89%, a positive predictive value of 67% and a negative predictive value of 97% for this test and suggested a normal BET might exclude a defecatory disorder. 5 However, Rao et al 10 found that many patients with dyssynergia could expel the balloon and they described a contradictory view that a normal test could not exclude the possibility of a defecatory disorder.…”
Section: How To Interpret the Balloon Expulsion Time And Its Clinicalmentioning
confidence: 99%